Portrait of a sitter, possibly Aleksandr Nikolaevich Lebedev, 1910 (1910)
Black and white stereograph addressed to Georg Bredig (1868-1944) of a scientist, possibly Aleksandr Nikolaevich Lebedev (1869–1937) posing with a table of glassware and apparatuses. The work is signed by Peter Leitdorf, who may have been the photographer.
Keywords: Bredig, Georg, 1868-1944; Chemists; Chemistry, Physical and theoretical; Glassware; Scientific apparatus and instruments; Lebedev, Aleksandr Nikolaevich, 1869–1937